Reduction in the in vitro sensitivity oF Drechslera tritici-repentis, isolated from wheat, to strobilurin and triazole fungicides - Tonin,Rosane Baldiga (2017)
ABSTRACT Reports of failure in the chemical control of wheat yellow leaf spot led to determination of the sensitivity of Drechslera tritici-repentis (Dtr) to the fungicides quinone outside inhibitors (QoIs) and demethylation inhibitors (DMIs). The IC50 was obtained for strobilurins (azoxystrobin, kresoxim-methyl, picoxystrobin and pyraclostrobin) and for triazoles (cyproconazole, epoxiconazole, propiconazole, prothioconazole and tebuconazole), using five Dtr isolates. Seven concentrations of the fungicides were tested in the bioassay: 0.00; 0.01; 0.10; 1.00; 10:00 and 20.00 and 40.00 mg/L active ingredient (a.i.). Assays consisted of completely randomized design and four replicates. Each experiment was performed twice, using the average of the two tests for statistical analysis. The percentage inhibition data for conidial germination (QoIs) and for mycelial growth (DMIs) were subjected to logarithmic regression analysis, calculating the 50% inhibitory concentration (IC50) based on the generated equation. There was a reduction in the sensitivity of Dtr isolates to strobilurins. IC50 values ranged from 0.58 to > 40.00 mg/L. The lowest sensitivity of isolates was detected for azoxystrobin, kresoxim-methyl, picoxystrobin and trifloxystrobin. Pyraclostrobin was most efficient, showing IC50 between 0.58 and 1.03 mg/L. The IC50 ranged from 0.35 to 1.37 mg/L for epoxiconazole, from 0.49 to 1.28 mg/L for propiconazole and from 1.41 to 2.34 mg/L for tebuconazole. Prothioconazole was most potent, showing IC50 between 0.09 and 0.21 mg/L. The hypothesis that the control failure can be attributed to the reduced Dtr sensitivity to the fungicides QoIs and DMIs was confirmed.